Chagas disease: a report of 17 suspected cases in Japan, 2012–2017 - Imai, Kazuo (Trop Med Health, 2019)
BACKGROUND: There are no reports on the prevalence of Chagas disease in Japan. Furthermore, screening programs and access to diagnosis and treatment have not been established. This study aimed to clarify the prevalence of Chagas disease among suspected cases in Japan and provide the reference data required for disease control. METHODS: Seventeen patients with suspected Chagas disease in Japan between 2012 and 2017 were included in the study. Patients were diagnosed with Chagas disease based on the two different serological tests for antibodies to Trypanosoma cruzi. Real-time polymerase chain reaction assay and blood culture techniques were performed to confirm T. cruzi parasitemia. RESULTS: Of the 17 patients, 11 (64.7%) were immigrants from Latin America. Ultimately, 6 patients (35.3%) were diagnosed with Chagas disease. Of these 6 patients, median age was 53.5 years, 5 patients were immigrants from Latin American, and 1 was Japanese who had a congenital infection. T. cruzi parasitemia was confirmed in 4 patients (66.7%), and 5 (83.3%) were in the chronic phase (Chagas cardiomyopathy, 4; megacolon, 1). Two patients (33.3%) commenced benznidazole treatment. CONCLUSION: Our study showed that some patients of Chagas disease living in Japan are already in the chronic phase at diagnosis because of substantial diagnostic delays. Further epidemiological studies on the prevalence of Chagas disease and systematic screening programs for the Latin American population are needed.